Charges virtuais, narração e interculturalidade - Silva, Marcelo Rodrigo da (2010)
The virtuality and cyberspace have brought remarkable changes to communication and are still spaces in potential discovery and experimentation in contemporary regarded as Post-modern. The Virtual Charges are examples of this ongoing process and present as fruitful field for study of interculturality, from the analysis of the articulation of its structure signic in the translation process of cultural signs. Thus, the keynote of this research is to observe the Virtual Charge as the environment of the interculturality, through cultural signs designed and coded in translator's action of cartoonist.To do so, at first, will be investigated the potential of virtual support and the definitions of Virtual Charges, identifying the changes that have marked their language due to the change in support. At this point will be taken conceptualizations about cyberspace and the virtual environment and studied the settings on the Virtual Charges as part of opinionated journalism and literary genre; will also be identified the changes caused by the change to the virtual support, observing features characteristic of his language, like humor, parody and irony, coupled with the concept of dialogism. In the second chapter will be thorough the studies about the concept of mediasphere, and audiovisual language; will also be studied the links between semic hues that result in the articulation of language with cultural signs in the narrative. The third chapter will be done an application of the studies about semiosphere, as well as the concept of Translation Intersemiotic (IT) as moored Julio Plaza; will also be studied the speech of the charges using the concepts of mimesis and semiosis. In the fourth and final chapter will be done an explanation about the influence of the Territoriality on the approach of te charges and Will be further detailed the studies of the Interculturalism. In compliance with the elements and concepts studied, was observed that the translator action of the Virtual Charge provides the Interculturalism, in that the characters are imbued with cultural signs and carry meanings related to crops where they came from, whether these cultural signs revealed under hues semics sound, visual or verbal.